ANALISIS STRATEGI PARTNERSHIP DALAM MENCAPAI OKR PADA PERUSAHAAN PT. GITS INDONESIA - Rahmah Ambar Pramesti; Marsha Aulia Hakim; Shafira Sidratul Muntaha Siswanda (JURNAL LENTERA BISNIS, 2023)
This research explores the partnership strategy implemented by PT GITS Indonesia, a digital agency and IT consulting company, to achieve measurable goals through the Objective and Key Results (OKR) framework. This research uses a qualitative descriptive method to understand how PT GITS Indonesia implements partnerships with external partners, vendors, and IT education institutions to create synergies, increase innovation, and access new resources. The results showed that PT GITS Indonesia successfully utilized OKRs and partnership strategies with a measured and structured approach. They identified potential partners, monitored vendors, analyzed partner products, carefully drafted documents, searched for cooperation partners, and initiated new ideas. With this approach, PT GITS Indonesia increased sales, expanded market share, and improved customer experience, gaining a competitive advantage in the market. Practical suggestions include optimizing OKRs, strengthening partner collaboration, developing team skills, and maintaining an accurate database. Academically, PT GITS is advised to continue engaging in research and collaboration with universities and monitor legal changes to strengthen their reputation as a reliable and innovative business partner. Key words: Strategic Partnership, OKR, Marketing, Vendor